2017
DOI: 10.11114/jets.v5i7.2498
|View full text |Cite
|
Sign up to set email alerts
|

Repeated E-book Reading and Its Contribution to Learning New Words among Kindergartners

Abstract: The contribution of repeated e-book reading with and without word explanation support and its effect on receptive and expressive word learning among preschoolers was examined. Seventy-eight kindergartners were randomly divided into an experimental and a control group. The experimental group received two individual reading sessions of an e-book with a dictionary that provided word explanations. The children clicked on hotspots which provided the explanation two more times. The children thus heard the meaning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
(45 reference statements)
0
26
0
1
Order By: Relevance
“…Reading also provides opportunities for adults to personalize story content by connecting the text to children’s background knowledge, increasing story comprehension as well as language exposure (McKeown, Beck, Sinatra, & Loxterman, 1992). As Korat and colleagues state, “Shared book reading in early childhood is considered a promising context for promoting children’s language, especially vocabulary enrichment” (Korat, Kozlov-Peretz, & Segal-Drori, 2017, p. 60).…”
Section: The Benefits Of Reading To Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading also provides opportunities for adults to personalize story content by connecting the text to children’s background knowledge, increasing story comprehension as well as language exposure (McKeown, Beck, Sinatra, & Loxterman, 1992). As Korat and colleagues state, “Shared book reading in early childhood is considered a promising context for promoting children’s language, especially vocabulary enrichment” (Korat, Kozlov-Peretz, & Segal-Drori, 2017, p. 60).…”
Section: The Benefits Of Reading To Young Childrenmentioning
confidence: 99%
“…Studies comparing self-reading books on tablets to print books are fewer in number but still find ambivalent results on comprehension, recall, and vocabulary (O’Toole & Kannass, 2018; Reich, Yau, & Warschauer, 2016). However, some studies have observed longer reading times for e-books (Richter & Courage, 2017), more talk about the device than the story with tablets (Chiong, Ree, Takeuchi, & Erickson, 2012; O’Toole & Kannass, 2018; Parish-Morris, Mahajan, Hirsh-Pasek, Golinkoff, & Collins, 2013; Revelle & Bowman, 2017; Richter & Courage, 2017), and both greater distraction (Chiong et al, 2012; Piotrowski & Krcmar, 2017) and learning (Korat et al, 2017) from e-book enhancements/hotspots.…”
Section: E-book Researchmentioning
confidence: 99%
“…Four of the reviewed studies reported atypically large ES [ 20 , 21 , 48 , 51 ] if we compare them with the rest of the reviewed studies or previous research [ 12 , 13 , 14 ]. Ioannidis [ 54 ] points out that a single study cannot be seen in isolation and should be compared with the entire prior evidence on the same or similar questions.…”
Section: Resultsmentioning
confidence: 99%
“…Across the studies, four papers [ 19 , 20 , 21 , 47 ] reported a total of 330 students at risk for learning disabilities. A total of 24 students who were English Language Learners (ELLs) were reported in one paper [ 42 ], and the number of low-SES children reported in one paper was 78 [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation